Hidangan Buffet di Regular Event “Ramayana Night Market” Hotel Hyatt Regency Yogyakarta - Handayani Rahayuningsih; Bramanti Aditya (Sekolah Vokasi, Universitas Gadjah Mada, 2017)
Hyatt Regency Yogyakarta has strategies to increase the number of visitors to the hotel. One of the strategies made by Hyatt Regency Yogyakarta regular event “Ramayana Night Market